Hardin's imagined tragedy is pig shit: A call for planning to recenter the commons. (February 2020) - Brinkley, Catherine
Hardin was wrong. There was not a tragedy of overuse. The Commons were dismantled by the state to make room for the formal economy and higher income user groups. I revisit the history of the Commons as a central, planned space in cities in order to ask two main questions. First, what role did the Commons play for cities and how is its lost felt? Second, how might planning reintroduce the Commons? In response, this research builds a functional theory of self-sufficiency at multiple scales of governance based on the opportunities of the Commons. The conclusion charts an urgent agenda for planning practice during a global population phase shift as cities increasingly house a greater proportion of humanity.